Reflections on Islamic Feminist Exegesis of the Qur’an - Wadud, Amina 1952- (2021)
The chapter highlights the importance of lived realities to the hermeneutics of the Qur’an and questions the classical interpretation of the Qur’an, evidencing that the dominant and prolific model of centering analysis of the sacred text and religious practices around men and men’s experience. Discussing attitudes and specific Qur’an passages, neutral terminology in relation to creation and cosmology, the story of Lot/Lut, and themes such as the question of Shari‘ah, the paper offers a personal reflection on gender and Qur’anic or Islamic interpretative possibilities. The author also explains how she came to a theological perspective on the equality of gender and gender identity over the last two decades, and gives specific examples of a unique Qur’anic analysis.
Keywords: Feminism; Islam; Islamic Feminism; Qur’an; qur’an exegesis; Women